Kinetics of M1 muscarinic receptor and G protein signaling to phospholipase C in living cells - Falkenburger, Björn H; Jensen, Jill B; Hille, Bertil (The Journal of general physiology, 2010)
G protein-coupled receptors (GPCRs) mediate responses to external stimuli in various cell types. Early events, such as the binding of ligand and G proteins to the receptor, nucleotide exchange (NX), and GTPase activity at the Galpha subunit, are common for many different GPCRs. For G(q)-coupled M(1) muscarinic (acetylcholine) receptors (M(1)Rs), we recently measured time courses of intermediate steps in the signaling cascade using Förster resonance energy transfer (FRET). The expression of FRET probes changes the density of signaling molecules. To provide a full quantitative description of M(1)R signaling that includes a simulation of kinetics in native (tsA201) cells, we now determine the density of FRET probes and construct a kinetic model of M(1)R signaling through G(q) to activation of phospholipase C (PLC). Downstream effects on the trace membrane lipid phosphatidylinositol 4,5-bisphosphate (PIP(2)) and PIP(2)-dependent KCNQ2/3 current are considered in our companion paper in this issue (Falkenburger et al. 2010. J. Gen. Physiol. doi:10.1085/jgp.200910345). By calibrating their fluorescence intensity, we found that we selected transfected cells for our experiments with approximately 3,000 fluorescently labeled receptors, G proteins, or PLC molecules per microm(2) of plasma membrane. Endogenous levels are much lower, 1-40 per microm(2). Our kinetic model reproduces the time courses and concentration-response relationships measured by FRET and explains observed delays. It predicts affinities and rate constants that align well with literature values. In native tsA201 cells, much of the delay between ligand binding and PLC activation reflects slow binding of G proteins to receptors. With M(1)R and Gbeta FRET probes overexpressed, 10% of receptors have G proteins bound at rest, rising to 73% in the presence of agonist. In agreement with previous work, the model suggests that binding of PLC to Galpha(q) greatly speeds up NX and GTPase activity, and that PLC is maintained in the active state by cycles of rapid GTP hydrolysis and NX on Galpha(q) subunits bound to PLC.